2009
DOI: 10.1097/tp.0b013e3181ae3392
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Inhibits T-Cell Activation, Proliferation, Cytokine and Chemokine Production, and Host Alloresponses

Abstract: Background We previously showed that pirfenidone, an anti-fibrotic agent, reduces lung allograft injury/rejection. In this study, we tested the hypothesis that pirfenidone has immune modulating activities and evaluated its effects on the function of T cell subsets, which play important roles in allograft rejection. Method We first evaluated whether pirfenidone alters T cell proliferation and cytokine release in response to T cell receptor (TCR) activation, and whether pirfenidone alters regulatory T cells (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…In a bleomycin-induced murine pulmonary fibrosis model, pirfenidone also suppressed MCP-1 levels induced by bleomycin (28). An in vitro study further showed that pirfenidone inhibited T-cell receptor-induced production of multiple proinflammatory chemokines, including IP-10, MIP-1, and Mig, which suggests its inhibition of inflammatory cell recruitment (39). The functional phenotype of macrophages depends on the renal microenvironment, which changes during the pathological process (15).…”
Section: Discussionmentioning
confidence: 92%
“…In a bleomycin-induced murine pulmonary fibrosis model, pirfenidone also suppressed MCP-1 levels induced by bleomycin (28). An in vitro study further showed that pirfenidone inhibited T-cell receptor-induced production of multiple proinflammatory chemokines, including IP-10, MIP-1, and Mig, which suggests its inhibition of inflammatory cell recruitment (39). The functional phenotype of macrophages depends on the renal microenvironment, which changes during the pathological process (15).…”
Section: Discussionmentioning
confidence: 92%
“…The beneficial effect of pirfenidone may in part be associated with inhibition of the pro-apoptotic effect of TGF-β The significant renal protection noted with pirfenidone in rats was associated with down-regulation of cyclosporine-induced pro-apoptotic genes and significant reduction of apoptosis in the renal tubules and interstitium [46]. Moreover, pirfenidone may have immune modulating properties, including inhibition of T-cell activation, proliferation and attenuation of associated induction of multiple cytokines [47]. …”
Section: Preclinical Studies In Animal Models Of Renal Fibrosismentioning
confidence: 99%
“…Moreover, PFD delayed acute rejection and prolonged mouse heterotopic cardiac allograft survival (9). PFD protective properties are believed to be from its inhibition of profibrotic and inflammatory cytokines (5, 10, 11).…”
Section: Introductionmentioning
confidence: 99%